Comparative characteristics of the leaving of glutathione from cells of different types. - Melanova Nazira Rashidovna; Numonov Otabek Urmonovich (International Journal on Orange Technologies, 2020)
Glutathione (GSH) is a negatively charged tripeptide, which is a major determinant of the cellular redox state and defense against oxidative stress. It is assembled inside and degraded outside the cells and is released under various physiological and pathophysiological conditions. The GSH release mechanism is poorly understood at present. In our experiments, freshly isolated rat thymocytes were found to release GSH under normal isotonic conditions at a low rate of 0.8260.07 attomol/cell/min and that was greatly enhanced under hypoosmotic stimulation to reach a level of 6.160.4 attomol/cell/min. The swelling-induced GSH release was proportional to the cell density in the suspension and was temperature-dependent with a relatively low activation energy of 5.460.6 kcal/mol indicating a predominant diffusion mechanism of GSH translocation. The glutathione release rate from rat thymocytes was found to be 4-10 times higher compared to the human red blood cells. Cultured melanoma cells also exhibited substantial release of glutathione both in normal and hypoosmotic stress conditions